Design Mobile App for Increase the Visitor Museum using Gamification Method - Novian Adi Prasetyo; Suyoto Suyoto (Universitas Ahmad Dahlan, 2018)
The museum's tourism object currently has a low visitor level compared to other tourism objects, even though the museum's function is very important as an enhancer of people's cultural knowledge. Judging from the small level of visitors, it cannot be separated from the effects of the promotion carried out by the museum. From the surveys that have been conducted, museum promotion uses social media more directly to the public, banners, radio, television, blogs and internet social media. In this study, an application that serves to promote museums using gamification methods was designed, this method was chosen because of the many existing promotional techniques, there is still little promotion using game content, therefore the gamification method is expected to encourage the motivation of users to visit the museum. This application will provide convenience to the museum management to promote the museum with media game content without having to spend large development and maintenance costs.